Smart Agriculture Training to Increase Fish Productivity in Padamulya Ciamis Village, West Java, Indonesia - Aceng Sambas; Gugun Gundara; Sundarapandian Vaidyanatahan; Aan Andriana (International Journal of Research in Community Services, 2022)
The main problem of Padamulya Village is the lack of a technology utilization system in the field of fisheries. Fish farming systems still use conventional, so that monitoring of fish quality is limited in time and place. The main purpose of this service is to provide knowledge to the community related to smart agriculture technology in the fisheries sector in Padamulya Village to increase quality fish production. The training activity was held on December 10, 2019 in the Hall of the Muhammadiyah University of Tasikmalaya. The results of this service show that the community is starting to have knowledge and provide land to make ponds with smart agriculture technology.